The Study of Lexical Loss in Three Generations of Tai Dialects in Uttaradit Province - พร้อมเพรียง รุ่งรัชนี (Language and Linguistics, 2019)
The present research compares variation and language use across three Tai dialects (i.e., Kham Muang, Phuan and Lao) and within three different age groups. The data were elicited by interviewing language resource persons using word lists of lexical items shared among all three Tai dialects, totaling 400 lexical items. A total of 36 spoken language interviews, with both male and female participants, were sub-divided into three distinct age groups: an elderly group 60 years old and above, a middle-aged group 35-50 years old, and a young group 15-25 years old. Data elicited from the 4 language speakers of each age group (Kham Muang, Phuan and Lao; 3 language x 3 age group x 4 Tai dialects) indicated that some specific lexical items were rarely used among the speakers. Some items were only used by the elderly group while the middle-aged group and the young group hardly used them or had never heard of them. The findings suggest that lexical loss is expected to occur in the future of these Tai dialects.